Recruitments and selection process of Al-Arafah Islami Bank Limited (AIBL) - Shultana, Sheikh Israt Jahan (Brac University, 2022)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2022.